1999
DOI: 10.1016/s0002-9440(10)65216-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cell Cycle Regulators p27Kip1 and Cyclin E in Transitional Cell Carcinoma of the Bladder Correlates with Tumor Grade and Patient Survival

Abstract: The cyclin-dependent kinase inhibitor p27(Kip1) is a powerful molecular determinant of cell cycle progression. Loss of expression of p27(Kip1) has been shown to be predictive of disease progression in several human malignancies. In this study we investigated the expression of two key cell cycle regulators, p27(Kip1) and cyclin E, in the progression of transitional cell carcinoma of the bladder. An immunohistochemical analysis was conducted in a series of 50 bladder tumor specimens, including 3 metastatic lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
52
2
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 26 publications
9
52
2
1
Order By: Relevance
“…To our knowledge, only one study has evaluated the association of p27 expression with outcomes of patients treated with radical cystectomy to date. When evaluated in 26 patients treated with radical cystectomy and 23 patients treated with transurethral resection, Del Pizzo et al 24 reported that p27 expression progressively decreased with increasing tumor stage and was associated with increased all cause mortality in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one study has evaluated the association of p27 expression with outcomes of patients treated with radical cystectomy to date. When evaluated in 26 patients treated with radical cystectomy and 23 patients treated with transurethral resection, Del Pizzo et al 24 reported that p27 expression progressively decreased with increasing tumor stage and was associated with increased all cause mortality in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the expression of p27 Kip1 protein in TCC of the urinary tract, to our knowledge, only two reports have been published (15,16). Del Pizzo et al (15), using immunohistochemistry to examine 50 cases of TCC of the urinary bladder, reported that the expression of p27 Kip1 protein was significantly lower in the poorly differentiated tumors and was an independent predictor.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the expression of p27 Kip1 protein in TCC of the urinary tract, to our knowledge, only two reports have been published (15,16). Del Pizzo et al (15), using immunohistochemistry to examine 50 cases of TCC of the urinary bladder, reported that the expression of p27 Kip1 protein was significantly lower in the poorly differentiated tumors and was an independent predictor. However, Kuczyk et al (16), who used immunohistochemistry to examine 50 cases of muscle-invasive bladder carcinoma, failed to find a relationship between a low expression of p27 Kip1 protein and either disease-free or overall survival, although the expression of p27 Kip1 protein was related to stage and grade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in patients with advanced, suboptimally debulked ovarian epithelial cancers, high cyclin E expression has remained an independent poor prognostic factor (Farley et al, 2003). Cyclin E overexpression has similarly been linked to adverse outcomes in patients with gastric (Jang et al, 1999), bladder (Del Pizzo et al, 1999) and non-small-cell lung carcinomas (Fukuse et al, 2000;Mishina et al, 2000;Muller-Tidow et al, 2001). …”
Section: Introductionmentioning
confidence: 99%